Fashion myths : a cultural critique (2013)
This cultural critique of fashion from philosophic-anthropological perspective is of special interest for researchers and students in the fields of Cultural Studies, Media Studies, Marketing, Advertising, Fashion, Cultural Critique, Philosophy, Sociology, Anthropology and Psychology, and for anyone interested in the ways in which fashion operates. Fashion is usually conceived as something superficial and ephemeral while a number of eminent philosophical accounts (e.g. Plato and Aristotle) tried to seek for an eternal truth behind the ever changing phenomena in our everyday life.2 A critical inquiry into fashion reveals what can be found behind fashion: something about that being, which consumes, creates and criticises fashionable items and services. Fashion as a cultural phenomenon is a manifestation of human needs and artistic-entrepreneurial creativity.